A steroid-inducible gene expression system for plant cells - Schena, M; Lloyd, A M; Davis, R W (Proceedings of the National Academy of Sciences - PNAS, 1991)
Promoters that allow the selective induction of gene expression in vivo constitute an important methodology in eukaryotic organisms such as yeast and the fruit fly, but to date no such system has been described for higher plants. Given the fact that mammalian steroid receptors can function as hormone-dependent inducers of gene expression in heterologous systems, the feasibility of using mammalian steroid hormones as selective inducers of plant gene expression was investigated. Here it is shown that the glucocorticoid receptor expressed in plant cells is capable of activating a test gene linked to glucocorticoid response elements, providing the transfected plant cells are treated with glucocorticoid hormone. Nanomolar concentrations of glucocorticoids are sufficient to induce gene expression more than 150-fold, without causing detectable alterations in the physiology of the cultured plant cells. These findings indicate that glucocorticoid induction of steroid-responsive promoters should provide a general method for regulating gene expression in plant cells and imply that such a system might ultimately function in whole plants such as Arabidopsis thaliana.